2023
DOI: 10.1037/per0000579
|View full text |Cite
|
Sign up to set email alerts
|

Is there a bias in the diagnosis of borderline personality disorder among racially minoritized patients?

Abstract: Empirical evidence documents disparities in the diagnosis of severe forms of psychopathology among racial/ethnic minority persons. However, research on diagnostic differences in personality disorders is equivocal: Some suggest higher prevalence of personality disorders among racial/ethnic minority persons, whereas other results suggest the opposite. The goal of the current study was to investigate (a) differences in the diagnosis of borderline personality disorder (BPD) in a mostly cisgender, heterosexual samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…(Zimmerman et al, 2021). The sample partially overlaps with other investigations also utilizing the PID-5-BF in this sample (Becker et al, 2022;Rodriguez-Seijas et al, 2020a, 2020b, 2021a.…”
Section: Participantssupporting
confidence: 53%
See 2 more Smart Citations
“…(Zimmerman et al, 2021). The sample partially overlaps with other investigations also utilizing the PID-5-BF in this sample (Becker et al, 2022;Rodriguez-Seijas et al, 2020a, 2020b, 2021a.…”
Section: Participantssupporting
confidence: 53%
“…The Norwegian PID-5-BF was found invariant between Norwegian-speaking and English-speaking students (Thimm et al, 2017). In a clinical sample, the PID-5-BF items were largely invariant when comparing non-Hispanic White patients with Patients of Color (Becker et al, 2023). In addition, the PID-5 facet scales have been found invariant across clinical and nonclinical samples (Bach et al, 2018; Somma et al, 2019), across European cultures (Sorrel et al, 2021), and across sex assigned at birth (Suzuki et al, 2019).…”
Section: Examining Measurement Bias Through Measurement Invariancementioning
confidence: 98%
See 1 more Smart Citation
“…For example, women with BPD tend to endorse more internalizing symptoms, such as suicidal ideation, self-harming behaviors, feelings of emptiness, identity disturbance, and comorbid eating disorders, whereas men with BPD tend to endorse more externalizing symptoms, such as impulsivity, substance use, and comorbid antisocial and narcissistic personality disorders (Hoertel et al, 2014; Johnson et al, 2003; McCormick et al, 2007; Sansone & Sansone, 2011; Sher et al, 2019). Furthermore, two studies of treatment-seeking persons with BPD found that POCs with BPD tended to endorse greater affective intensity, emotion dysregulation, and thoughts of interpersonal aggression and fewer self-harming behaviors relative to their White counterparts (L. G. Becker et al, 2023; Newhill et al, 2009). In contrast, a study of incarcerated persons with BPD reflected no racial differences in likelihood of violent behavior, suggesting that these differences may not generalize to carceral settings (Yasmeen et al, 2022).…”
Section: Mental Health Inequities In Carceral Settingsmentioning
confidence: 99%
“…Bagby et al (2022) found evidence suggesting a lack of configural invariance across WA and BA groups in the United States, interpreting a single-factor solution for the BA group, suggestive of an undifferentiated, broadly based level of demoralization. On the other hand, Becker et al (2023) examined the PID-5 across a WA and non-White group (26% Black, 44% Hispanic, 11% Asian, 19% other), finding evidence of strong invariance. Clearly, more work is needed to examine the suitability of the instrument across race in the United States, particularly for BA populations.…”
Section: Pid-5 Factor Structure Replicabilitymentioning
confidence: 99%